Running a web design business. - Cubbon, Rob; Safari eBooks ([Place of publication not identified] : [Stone River eLearning], 2014)
"You can run your own web design business from home--all you need is a computer and an internet connection. My name is Rob Cubbon and I have been running a successful web design business for many years which turns in more profit year after year. How do I do it? Well, it's not because I'm the best designer in the world, that's for sure! ;) Here are some essential questions I'll answer for you: What software and hardware you will need to start and grow the business? How do you get clients? How you handle clients on email, on the phone in real life? Do you need contracts? If so, what you put in a contract. How do you get paid? What are the best ways to ensure you get paid properly and on time? If you really want to make money running a web design business then you'll have to offer a premium service to the best type of clients and I can show you how to do that. Course Features: Over 22 lectures and 6.5 hours of content!; To learn how to set up and run a web design business either part or full time."--Resource description page.
Title from title screen (viewed September 28, 2015).
Publisher and date of publication from resource description page.
Presenter, Rob Cubbon.
Keywords: Web site development; Web site development industry; Entrepreneurship; Electronic books